2019
DOI: 10.1101/694901
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Individual, but not population asymmetries, are modulated by social environment and genotype inDrosophila melanogaster

Abstract: Theory predicts that social interactions can induce an alignment of behavioral asymmetries between individuals (i.e., population-level lateralization), but evidence for this effect is mixed. To understand how interaction with other individuals affects behavioral asymmetries, we systematically manipulated the social environment of Drosophila melanogaster, testing individual flies and dyads (female-male, female-female and male-male pairs). In these social contexts we measured individual and population asymmetrie… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 100 publications
0
3
0
Order By: Relevance
“…Quantifying individual movement is essential for revealing the genetic (Kain et al, 2012; Brown et al, 2013; Ayroles et al, 2015) and environmental (Bierbach et al, 2017; Akhund-Zade et al, 2019; Versace et al, 2019) underpinnings of phenotypic variation in behavior—as well as the phylogeny of behavior (e.g., Berman et al, 2014a). Measuring individual behavioral phenotypes requires tools that are robust, scaleable, and easy-to-use, and our approach offers the ability to quickly and accurately quantify the behavior of many individuals in great detail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantifying individual movement is essential for revealing the genetic (Kain et al, 2012; Brown et al, 2013; Ayroles et al, 2015) and environmental (Bierbach et al, 2017; Akhund-Zade et al, 2019; Versace et al, 2019) underpinnings of phenotypic variation in behavior—as well as the phylogeny of behavior (e.g., Berman et al, 2014a). Measuring individual behavioral phenotypes requires tools that are robust, scaleable, and easy-to-use, and our approach offers the ability to quickly and accurately quantify the behavior of many individuals in great detail.…”
Section: Discussionmentioning
confidence: 99%
“…However, because animals exhibit different behaviors depending on their surroundings (Strandburg-Peshkin et al, 2017; Francisco et al, 2019; Akhund-Zade et al, 2019), laboratory environments are often less than ideal for studying many natural behaviors. Most conventional computer vision methods are also limited in their ability to accurately track groups of individuals over time, but nearly all animals are social at some point in their life and exhibit specialized behaviors when in the presence of conspecifics (Strandburg-Peshkin et al, 2013; Rosenthal et al, 2015; Jolles et al, 2017; Klibaite et al, 2017; Klibaite and Shaevitz, 2019; Francisco et al, 2019; Versace et al, 2019). These methods also commonly track only the animal’s center of mass, which reduces the behavioral output of an individual to a two-dimensional or three-dimensional particle-like trajectory.…”
Section: Introductionmentioning
confidence: 99%
“…Based on their antipredatory and affiliative behaviour, it has been suggested that animals located in an open field with other conspecifics experience both the fear of being in an open environment – which has the effect of reducing activity and exploration –, and social reinstatement, namely the motivation to reach the group and remain in contact with conspecifics (Suarez & Gallup, 1983; Vallortigara, 1992; Vallortigara, Cailotto, & Zanforlin, 1990). In a range of species, greater latency of movement/tonic immobility indicates antipredatory responses, while shorter distance between individuals indicates stronger social/reinstatement motivation (Jones, Mills, & Faure, 1996; Versace, Caffini, Werkhoven, & Bivort, 2019).…”
Section: Introductionmentioning
confidence: 99%